Effects of Food Provisioning on the Daily Ration and Dive Site Use of Great Hammerhead Sharks, Sphyrna mokarran - Heim, Vital; Dhellemmes, Félicie; Smukall, Matthew J.; Gruber, Samuel H.; Guttridge, Tristan L. (Frontiers in Marine Science, 2021)
Wildlife provisioning is popular, economically valuable and a rapidly growing part of marine tourism, with great potential to benefit conservation. However, it remains controversial due to limited understanding of its implications on the behavior and ecology of target species. In this study we modelled how various abiotic and biotic factors influenced great hammerhead sharks’ (Sphyrna mokarran) use of a recreational dive site in Bimini, the Bahamas, where shark-feeding has been conducted since 2012. Further, we used bioenergetics modelling to estimate their daily ration and examined if individual sharks fulfilled their daily energetic requirements from food uptake during dives. Between December 2016 and May 2017, we collected data during 104 provisioning dives in collaboration with a local dive operator. Twenty-eight individual great hammerhead sharks were observed, 11 were philopatric (i.e. identified at the dive site in previous years), and 17 were new (i.e. identified at the dive site for the first time during this study) individuals. On average, four sharks were observed daily, occasionally up to 9 individuals, with some individuals spending more than 2 hours attending each dive, consuming up to 4.75 kg of provisioned food per dive and returning repeatedly throughout the study period. When we grouped sharks based on their previous experience of the dive site (i.e. philopatric vs. new sharks) we found significantly higher attendance indices, i.e. the number of attended dives divided by the total number dives, and longer presence times during dives in philopatric sharks and different responses towards the number of boats and conspecifics between the two groups. Overall, great hammerhead sharks increased their bait uptake during longer dives and when more boats were present at the dive site. Finally, 9 of 12 provisioned great hammerhead sharks were regularly able to fuel their daily energetic requirements from provisioned food alone, with two sharks doing so on 77.8 % of all dives. Our study provides insights into how large-bodied marine predators react towards wildlife tourism associated provisioning and allows further discussion about daily energy uptake during provisioning dives, its potential impacts on the ecological role of the target species and associated management measures.